Intelligent Mobile Models and Their Application in the Educational Process - Alkhanova, Gulnur; Zhuzbayev, Serik; Syrkin, Iliya; Kurmangaliyeva, Nurgul (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Using ICTs in education allows the effective integration of new technologies into the educational process. Developing information and communication technologies also require timely changes in knowledge evaluation and use. As a result, methods, techniques, and technologies used in learning are being updated. In this study, a method for developing an automated educational and methodical complex based on a semantic network is described. Requirements for such educational and methodological complex have been formulated. Structural and formal models of tools based on a semantic network have been presented. The purpose of developing the model is to make it easier for students to perceive the various educational and methodological complexes through its compilation on the basis of a holistic view of the subject area, as well as to optimize the work of the teacher.